Midwifery education, regulation and association in the Democratic Republic of Congo (DRC) - current state and challenges - Malin Bogren; Britou Ndela; Carla Toko; Marie Berg (Taylor & Francis Group, 2020)
Background: In the Democratic Republic of Congo (DRC), maternal and neonatal health outcomes are poor and delivering healthcare services of sufficient quality is a challenge as there are only 0.6 midwives, physicians, or nurses for every 1,000 inhabitants. Objective: To explore the current state of the midwifery profession in the DRC and to suggest suitable strategies for increasing the quality and quantity of a highly competent midwifery health workforce in the DRC. Methods: Data were collected at a workshop with 17 key persons using three questionnaires developed by the International Confederation of Midwives, and three focus group discussions. The analysis was focusing on quantitative and qualitative content. Results: In DRC the midwife profession is not legislated. A midwifery association is well established, but due to a lack of resources does not function optimally. Two midwifery education programmes exist: a three-year direct-entry programme resulting in a diploma in midwifery, and a 12-month postgraduate programme for nurses resulting in a certificate in midwifery. Neither of the programmes leads to a bachelor's or master's degree. At the institutions offering the midwifery programmes (n = 16), the educators' academic qualifications are lower than required and there is a lack of teaching and training equipment for meeting the education needs. Conclusions: The Sustainable Development Goal on health, and specifically the health of mother and newborn, will be difficult to meet in the DRC. We therefore suggest that (i) the midwifery education programmes be improved to meet international standards; (ii) these programmes be designed in a way that allows for an academic degree at either the bachelor's or master's level; (iii) the competence level of the midwifery educators be increased; and, most crucially, (iv) a regulatory structure be formed that legislates and regulates the midwifery profession and its autonomous practice.